Correlative SICM‐FCM reveals changes in morphology and kinetics of endocytic pits induced by disease‐associated mutations in dynamin. Issue 7 (24th April 2019) - Ali, Tayyibah; Bednarska, Joanna; Vassilopoulos, Stéphane; Tran, Martin; Diakonov, Ivan A.; Ziyadeh-Isleem, Azza; Guicheney, Pascale; Gorelik, Julia; Korchev, Yuri E.; Reilly, Mary M.; Bitoun, Marc; Shevchuk, Andrew
ABSTRACT: Dynamin 2 (DNM2) is a GTP‐binding protein that controls endocytic vesicle scission and defines a whole class of dynamin‐dependent endocytosis, including clathrin‐mediated endocytosis by caveoli. It has been suggested that mutations in the DNM2 gene, associated with 3 inherited diseases, disrupt endocytosis. However, how exactly mutations affect the nanoscale morphology of endocytic machinery has never been studied. In this paper, we used live correlative scanning ion conductance microscopy (S1CM) and fluorescence confocal microscopy (FCM) to study how disease‐associated mutations affect the morphology and kinetics of clathrin‐coated pits (CCPs) by directly following their dynamics of formation, maturation, and internalization in skin fibroblasts from patients with centronuclear myopathy (CNM) and in Cos‐7 ce1ls expressing corresponding dynamin mutants. Using S1CM‐FCM, which we have deve1oped, we show how p.R465W mutation disrupts pit structure, preventing its maturation and internalization, and significantly increases the lifetime of CCPs. Differently, p.R522H slows down the formation of CCPs without affecting their internalization. We also found that CNM mutations in DNM2 affect the distribution of caveoli and reduce dorsal ruffling in human skin fibroblasts. Collective1y, our S1CM‐FCM findings at single CCP leve1, backed up by electron microscopy data, argue for the impairment of several forms of endocytosis in DNM2 ‐linked CNM.—Ali, T., Bednarska, J., Vassilopoulos, S., Tran, M., Diakonov, I. A., Ziyadeh‐Isleem, A., Guicheney, P., Gorelik, J., Korchev, Y. E., Reilly, M. M., Bitoun, M., Shevchuk, A. Correlative SICM‐FCM reveals changes in morphology and kinetics of endocytic pits induced by disease‐associated mutations in dynamin. FASEB J. 33, 8504–8518 (2019). www.fasebj.org